Communication and regulatory challenges in the Baltic Sea region ports – Update 2020 - Vesa Kilpi (Hazard Project, 2022)
Over the years, IMO, EU and national authorities have issued an extensive body of regulations, standards, and legislation concerning the prevention of accidents in the shipping of dangerous goods, and actions to be taken should the worst happen at seaports.
In 2017, Ajokas & Laakso (2017) carried out a Delphi study for the HAZARD project to identify the challenges in the implementation and communication of the safety and security regulations and accident communication at seaports in the Baltic Sea Region. The report at hand is a status follow-up for the Ajokas & Laakso (2017) study. In this study, the current state is also compared to the 2017 results.
A survey questionnaire was sent in June 2020 to over 100 seafaring and seaport organizations and authorities operating in the Baltic Sea Region. A total of 43 replies was received from seaport and shipping operators, research institutes, and authorities.
Results of the new survey indicate progress both in implementation and communication when compared to the results of the earlier study. In spite of clear progress, there is still work to do. Interpretation and terminology of regulations and rules vary between countries and regions. Also, the integration of various communication systems should be better, and seaport site information availability should be improved. At seaports, the increasing automation in vessels and seaports should be included in safety and security planning already now.